Metal-free C8–H functionalization of quinoline N-oxides with ynamides. Issue 57 (22nd June 2021) - Hu, Weican; Zhang, Feiyang; Chen, Chen; Qi, Tianhang; Shen, Yanlong; Qian, Guoying; Rong, Zhouting
Abstract : A metal-free C8–H functionalization of quinoline N -oxides with ynamides was developed. Abstract : The metal-free C8–H functionalization of quinoline N -oxides with ynamides is unveiled for the first time by the intramolecular Friedel–Crafts-type reaction of quinolyl enolonium intermediates generated from Brønsted acid-catalyzed addition of quinoline N -oxides to ynamides. Various quinoline N -oxides and terminal ynamides prove to be suitable substrates for this method. A one-pot protocol was then developed for the metal-free direct C8–H functionalization of quinolines.